Mathematical statistics: Basic ideas and selected topics - Bickel, Peter J.; Doksum, Kjell A. (London CRC press, 2016)
Presents fundamental, classical statistical concepts at the doctorate level without using measure theory. It gives careful proofs of major results and explains how the theory sheds light on the properties of practical methods. Volume II covers a number of topics that are important in current measure theory and practice. It emphasizes nonparametric methods which can really only be implemented with modern computing power on large and complex data sets. In addition, the set includes a large number of problems with more difficult ones appearing with hints and partial solutions for the instructor
Keywords: Statistical science; Mathematical statistics; Basic ideas of statistical science